PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS I SDN 77 PEKANBARU - Hatma Hatma; Jesi Alexander Alim; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of the problem in this research is the low result of learning math grade I SD Negeri 77 Pekanbaru, caused by the applied learning strategies teachers are less precise. The action taken is the implementation of Direct Learning Model. This research aims to improve the results of learning math grade I in the SD Negeri 77 Pekanbaru school year 2014/2015. Design research is the Research Action class (PTK). The research was conducted in two cycle with data collection instruments namely observation sheets teachers and students as well as test results of learning. After the applied learning models direct then the results of the study showed that application of the Model of Direct Learning can improve the results of learning math grade IV SD Negeri 77 Pekanbaru.Keywords: Direct Learning, Student Achievement The Result of Mathematics Studies.